Exploring the Effects of Osteopathic Manipulative Treatment on Autonomic Function Through the Lens of Heart Rate Variability - Carnevali, Luca; Lombardi, Luca; Fornari, Mauro; Sgoifo, Andrea (Frontiers in Neuroscience, 2020)
The osteopathic community has long hypothesized that the autonomic nervous system (ANS) represents one of the putative substrates through which osteopathic manipulative treatment (OMT) can improve body functions that have been altered by musculoskeletal alterations. Heart rate variability (HRV) is an important physiological measure of cardiac ANS activity. Emerging evidence suggests that OMT is associated with HRV changes that (i) are indicative of a larger cardiac vagal modulation, (ii) are independent from the part of the body needing treatment, (iii) occur even in the absence of musculoskeletal alterations. Yet, many questions remain unanswered, the duration of these effects and the specificity of HRV responses to different OMT techniques being perhaps the most critical. Therefore, this paper discusses prospects for future applications of HRV for the study of the influence of OMT on ANS function. Moreover, based on existing studies and preliminary data on the effects of OMT on HRV in specific pathological (hypertension) and physiological (stress exposure and recovery from sport competition) conditions that are commonly associated with increased sympathetic and/or decreased vagal activity, we propose that HRV analysis could be exploited to evaluate the effectiveness of OMT as a preventive or complementary strategy in clinical and non-clinical conditions characterized by ANS imbalance.